1993
DOI: 10.1111/j.1549-0831.1993.tb00484.x
|View full text |Cite
|
Sign up to set email alerts
|

Development and Social Problems: The Impact of the Offshore Oil Industry on Suicide and Homicide Rates1

Abstract: There are few studies in the literature concerning economic development that examine the impact of offshore oil and gas extraction on communities and even fewer that use annual data, examine more than one community and account for the degree of involvement of the community in the oil industry. This study rectifies these problems. The results support hypotheses derived from social disorganization and relative deprivation theories by demonstrating that higher levels of and rapid changes in development are associ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(14 citation statements)
references
References 39 publications
1
13
0
Order By: Relevance
“…Echoing the outcomes of previous authors (Kohrs 1974;Seydlitz et al 1993), the exploration of suicide rates in the Bakken found a noteworthy increase in an area experiencing rapid economic growth. While North Dakota as a whole has experienced a major increase in suicide rates over the past decade (Daily Mail 2013), the Bakken region has experienced an increase even greater than the state as a whole.…”
Section: Summary and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Echoing the outcomes of previous authors (Kohrs 1974;Seydlitz et al 1993), the exploration of suicide rates in the Bakken found a noteworthy increase in an area experiencing rapid economic growth. While North Dakota as a whole has experienced a major increase in suicide rates over the past decade (Daily Mail 2013), the Bakken region has experienced an increase even greater than the state as a whole.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…Multiple authors maintain large scale industrial development has a detrimental effect on the mental health of and psycho-social well-being of community members (Freudenburg, Bacigalupi, Landoll-Young 1982;Jacquet 2014). Also common are findings of increased rates of suicide attempts (Kohrs 1974) and suicide (Seydlitz et al 1993). These findings seem to reiterate Durkheim's ([1897Durkheim's ([ ]1951 warning that "a state of exasperation and irritated weariness" (p.357) in anomic areas exists which contributes to increased rates of suicide and other harmful behaviors.…”
Section: Boomtown Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the first explicit adoption of social disorganisation theory to the study of communities and rural crime was an article published in Rural Sociology in 1993 on how off-shore oil development impacts rural parishes (equivalent to a county) in Louisiana, a state in the southern region of the United States (US) (Seydlitz, Laska, Spain, Triche and Bishop 1993). The authors describe social disorganisation theory in a way similar to Kubrin's (2009) summative statement:…”
Section: Criticising: the Rural Community And Crimementioning
confidence: 99%
“…The Seydlitz et al (1993) article was the beginning of a steady parade of published studies of rural communities and crime utilizing social disorganisation theory or a closely related variant (Barnett and Mencken 2002;Bouffard and Muftić 2006;Cancino 2005;Ceccato and Dolmen 2011;Deller and Deller 2010; Donnermeyer, Jobes and Barclay 2009;Jobes 1999;Jobes Barclay, Weinand and Donnermeyer 2004;Jobes, Donnermeyer and Barclay 2005;Kaylen 2010;Kaylen and Pridemore 2011Lee 2006Lee , 2008 Bartkowski 2004A, 2004b;Lee, Maume and Ousey 2003;Lee and Ousey 2001;Lee and Thomas 2010;Li 2012;Mencken and Barnett 1999;Osgood and Chambers 2000;Ousey and Lee 2010; Resig and Cancino 2004;Spano and Nagy 2005;Tunnell 2006; Weisheit 2004, 2012). To a great extent, this 2 Portions of this paper are from two sources: (1) …”
mentioning
confidence: 99%